Superelastic Ti-18Zr-12.5Nb-2Sn (at.%) alloy scaffolds with high porosity fabricated by fiber metallurgy for biomedical applications. (December 2019) - Li, Shuanglei; Kim, Yeon-wook; Choi, Mi-seon; Nam, Tae-hyun
Abstract: β-type Ni-free Ti-based alloys are promising materials for biomedical applications. In this study, highly porous Ti-18Zr-12.5Nb-2Sn (at.%) alloy scaffolds with a porosity of about 80% were fabricated by a process of combining rapid solidification method and fiber metallurgy technique for the replacement of damaged human cancellous bone. Alloy fibers were produced by melt overflow technique. Phase identifications of alloy fiber and scaffold were studied by X-ray diffraction (XRD). Transformation behavior and microstructure of alloy fiber were investigated by differential scanning calorimetry (DSC) and transmission electron microscope (TEM), respectively. Superelastic behavior of alloy fiber was investigated by the dynamic mechanical analyzer (DMA). Porous structure of scaffold was observed by scanning electron microscope (SEM). The mechanical properties and superelasticity of scaffold were investigated by compressive test. The rapidly-solidified fiber consisted of β phase, athermal ω phase and nanodomains. Clear superelastic behavior with the recoverable strain of 4.5% for 5% pre-strain was observed in rapidly-solidified alloy fiber. Three-dimensional networks with fiber-fiber sintering joints were observed in the as-sintered scaffold which consisted of predominant β phase, α phase and isothermal ω phase. The scaffold annealed at 973 K consisted of single β phase. Stress-induced martensitic transformation of β→α " occurred during the compressive test. The compressive plateau stress and elastic modulus of the as-sintered and annealed scaffold were found to be 7.9 MPa and 0.43 GPa, 7.4 MPa and 0.41 GPa, respectively, similar to those of cancellous bone. A recoverable strain of 3.4% was observed in the annealed scaffold at body temperature (310 K). Highlights: Novel Ti-Zr-Nb-Sn scaffold with high porosity of about 80% was prepared by fiber metallurgy. Large recoverable strain of 3.4% was obtained in the annealed scaffold at body temperature. The annealed scaffolds showed elastic modulus of 0.41 GPa, similar to that of cancellous bone. Rapidly-solidified alloy fibers showed clear superelasticity at room temperature. α phase and isothermal ω phase were observed in the as-sintered scaffold.